Fantasy Theme on the Replication of Yang Terdalam on TikTok - Tanjung, Sumekar (International Journal of Media and Communication Research, 2023)
This study aims to explain the fantasy theme on the replication of the song Yang Terdalam. The background of this research is the high trend of the replication from December to January 2022 on TikTok. Users on TikTok have their own identity. Identity is an absolute requirement for a user to participate in social networking services. In addition, participation is an indicator of active users in digital culture or a culture where people can produce and consume, distribute and replicate memes in their own way. This shows that users as cultural prosumers do both production and consumption in replicating memes. They dramatize messages into fantasy chains to create effective, fun, entertaining communication and build relationships between users. The author applied a descriptive approach and a conversational analysis method with fantasy theme analysis techniques. User comments are narratives that explain the dramatic message conveyed by the user. The research object is three video replications on TikTok. The results showed three fantasy themes, namely resistance to performance hegemony which was built by two types of fantasy, there are constructive satire on ugliness and metaphors of anime characters, objectification of disabilities, and domestication of women. This suggests that a fantasy can be a situation where the rhetoric is repeated within the group. When fantasy becomes a rhetorical vision, users have created dramatization